Coping with technostress induced by social networking services - Ikävalko, Jyri (My University, 2024)
Social networking services (SNSs) have become some of the most used IT applications worldwide. The experience of stress when using IT, or technostress, has been established as a negative and potentially harmful phenomenon affecting SNS users. Prior research on how IT users can attempt to mitigate their technostress has mostly addressed organizational contexts, and there is a lack of research on how SNS users specifically deal with this problem. The empirical part of this thesis attempts to bridge this gap in the literature by uncovering coping methods ordinary SNS users utilize to mitigate technostress. The study draws from coping theory to frame coping behaviors as emotion-focused or problem- focused attempts to reduce stress. A qualitative approach is adopted by conducting 7 interviews with SNS users with experience using coping techniques to address their technostress. The results of the study provide preliminary evidence that SNS users can alleviate some forms of technostress by directly addressing the problem by preventing SNS use or adjusting their emotional response by either prioritizing their time use or adjusting their attitude. A pattern of SNS-related technostress diminishing from teenage years to early adulthood was also found, which was attributed to aging and maturing. Finally, despite finding success with utilizing coping techniques, deficiencies in their effectiveness were identified. The results of the study complement existing technostress research by investigating technostress mitigation in the context of SNS use. They can also inform other SNS users of potential ways they can employ coping strategies to reduce the harmful impacts of technostress.
Keywords: technostress, coping, social networking services